2005
DOI: 10.1038/sj.bmt.1704960
|View full text |Cite
|
Sign up to set email alerts
|

Optimal initial dose of oral cyclosporine in relation to its toxicities for graft-versus-host disease prophylaxis following reduced-intensity stem cell transplantation in Japanese patients

Abstract: Summary:Since the introduction of reduced-intensity stem-cell transplantation (RIST), allogeneic stem-cell transplantation has become available for elderly patients. While pharmacokinetics of cyclosporine might differ according to age or other factors, cyclosporine is uniformly started at an oral dose of 6 mg/kg/day. We retrospectively reviewed medical records of 35 patients aged between 32 and 65 (median 52) years who had undergone RIST. Doses of cyclosporine were adjusted to the target blood trough level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…There was a predominance of cohort studies, 9,10,17,19,21–33 which were classified according to their scientific evidence as level 2B. In other words, they are trustworthy and good quality studies; thus, it is highly unlikely that new studies can show substantial changes regarding effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a predominance of cohort studies, 9,10,17,19,21–33 which were classified according to their scientific evidence as level 2B. In other words, they are trustworthy and good quality studies; thus, it is highly unlikely that new studies can show substantial changes regarding effects.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies (89.5%) indicated an incidence of nephrotoxicity of more than 30%. 9,10,17–21,23–27,29–33 In other words, nearly one-third of patients undergoing HSCT and exposed to cyclosporine at doses from 5.0 to 12.5 mg/kg/day by oral administration developed some sort of kidney dysfunction. Cyclosporine was considered a risk factor for nephrotoxicity in 31.6% of the investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine 3 mg/kg continuous infusion was initiated for GVHD prophylaxis from day 1, and this was switched to oral administration when patients tolerated oral intake. The doses were adjusted with its whole blood levels [31]. Nine patients received additional short-term methotrexate (10 mg/m 2 on day 1 and 7 mg/m 2 on days 3 and 6).…”
Section: Transplantation Proceduresmentioning
confidence: 99%
“…CsA PKs barely studied in neonatal population. Along with introduction of reduced-intensity stem cell transplantation, more elderly patients have become candidates for allogeneic transplant [59] but data for elderly patients are limited as well. Some studies revealed that cyclosporine PKs is not different in elderlies compared with young adults but other observations including consequential toxicities have been controversial [59,93,[95][96][97] and accordingly some authors stated in favor of implementation of lower dosing and target levels in geriatrics [95].…”
Section: Hsct Population Specificationsmentioning
confidence: 99%
“…The consistency with Neoral has provided the chance of starting immunomodulations with oral cyclosporine at early periods of transplantation process, reducing the need for initial iv. therapy [59][60][61][62][63][64][65]. Two other cyclosporine oral product brands, Cipol N ® and Equtrol ® demonstrated bioequivalency with Neoral [3, [66][67].…”
Section: Formulation Differencesmentioning
confidence: 99%